Online interaction codesign: an experience report with elderly women - Rosa, Valéria Argôlo; Matos, Ecivaldo De Souza; Zabot, Diego; Dos Santos, Juliana Maria Oliveira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
The recognition of the need to include older people in design processes is something already established by the scientific community. However, studies involving older people in interaction design processes are usually conducted with co-located participants. With the Pandemic by Covid-19, research with participatory practices, including participatory/codesign techniques and methods, had to be adapted to the online mode; thus, it is a significant challenge for research involving older people. Therefore, it became necessary to understand how older people can participate in an online interaction codesign process. In this sense, this article presents an experience report on the conduction of an interaction codesign process carried out online with/by five women, mostly elderly. Part of a more considerable investigation, this experience was conducted through a five-step interaction co-design process, with techniques and methods adapted to the online context. Throughout the execution of the process, the women expressed themselves in a creative and collaborative way, becoming design partners in the definition, ideation, prototyping and evaluation of a mobile application aimed at their needs. In this regard, when reflecting on the experience, some challenges were noticed, such as distractions caused by external noises, family interference, and Internet connection problems. On the other hand, some positive elements can also reverberate in the process co-located interaction design, such as encouraging participation through praise for each victory achieved, in the face of difficulties encountered, and through words of confidence. It is hoped that the shared experience in this account will contribute to future initiatives and studies aiming to engage elderly individuals in participatory processes conducted online.